Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.6964
|View full text |Cite
|
Sign up to set email alerts
|

Ab0969 comparison Among Acr1997, Slicc and the New Eular/Acr Classification Criteria in Childhood-Onset Systemic Lupus Erythematosus

Abstract: BackgroundTo date there are no specific classification criteria for childhood-onset systemic lupus erythematosus (cSLE).ObjectivesThis study aims to compare the performance among the American College of Rheumatology (ACR) 1997, the Systemic Lupus International Collaborating Clinics criteria (SLICC) and the new European League Against Rheumatism (EULAR)/ACR criteria, in a cSLE cohort.MethodsData were retrospectively collected from medical charts of cSLE cases and controls with defined rheumatic diseases, both A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Another study showed the same sensitivity for 2019-EULAR/ACR and 2012-SLICC criteria (97.4%) and it was higher compared with the 1997-ACR criteria in cSLE patients (87.2%), with similar specificity between 2012-SLICC and 2019-EULAR/ACR criteria (98.4% and 99.7%, respectively) [ 92 ]. Fonseca et al showed that a 2019-EULAR/ACR total score ≥ 13 was more appropriate to classify Brazilian cSLE patients than the proposed score of ≥ 10 and that 2012-SLICC criteria better scored for cSLE at the first visit and 1-year-follow-up [ 93 ].…”
Section: Childhood-onset Systemic Lupus Erythematosus (Csle) Stratification and New Validated Classification Criteriamentioning
confidence: 99%
“…Another study showed the same sensitivity for 2019-EULAR/ACR and 2012-SLICC criteria (97.4%) and it was higher compared with the 1997-ACR criteria in cSLE patients (87.2%), with similar specificity between 2012-SLICC and 2019-EULAR/ACR criteria (98.4% and 99.7%, respectively) [ 92 ]. Fonseca et al showed that a 2019-EULAR/ACR total score ≥ 13 was more appropriate to classify Brazilian cSLE patients than the proposed score of ≥ 10 and that 2012-SLICC criteria better scored for cSLE at the first visit and 1-year-follow-up [ 93 ].…”
Section: Childhood-onset Systemic Lupus Erythematosus (Csle) Stratification and New Validated Classification Criteriamentioning
confidence: 99%
“…An alternative threshold for the new EULAR/ ACR-2019 criteria has been suggested for application in juvenile SLE patients, where a score of ≥13 has been associated with increased specificity, positive predictive value, and overall accuracy as a cut-off point. 5,39 Nonetheless, additional research is needed to assess the impact of the EULAR/ACR-2019 criteria in the context of children, particularly given that younger children with childhood-onset systemic lupus erythematosus often exhibit lower rates of ANA positivity. 30 The treatment of lupus nephritis is a particularly prominent aspect in treatment for cSLE.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood-onset SLE is associated with severe organ involvement, higher disease activity, and greater damage at diagnosis compared to adult patients [25]. There are few studies in the literature evaluating the performance of ACR/EULAR-2019 criteria in juvenil SLE [2,8]. In one of these studies, 122 childhood-onset SLE patients and 89 controls (ANA positive with other rheumatic diseases) were compared.…”
Section: Discussionmentioning
confidence: 99%